Histopathological Study for the Effect of Ethanolic Extract of Sonchus Oleraceus on Escherichia Coli Bacteria in Mice: Zainab R. Zghair, Aseel M. Hamzah and Mohmmed J. Alwan - Alwan, Mohammed J. (The Iraqi Journal of Veterinary Medicine, 2013)
This study was designed to explore the effect of the ethanolic extract of Sonchus oleraceus on Escherichia coli infection in mice. The LD50 of the orally dosage ethanolic extract of Sonchus oleraceus was found to be 800gm/kg B.W for two weeks. Twenty five mice were randomly divided into five groups. The first group was given orally the ethanolic extract with dose 800 mg/kg B.W for two weeks, then infected with Escherichia coli bacteria with dose 1×108 cfu for ten days. Second group was infected with Escherichia coli bacteria with dose 1×108 cfu for ten days then treated with ethanolic extract of Sonchus oleraceus for two weeks. The third group was infected only with Escherichia coli bacteria with a dose 1×108 cfu for ten days. Fourth group was given orally the ethanolic extract with a dose 800 mg/kg B.W orally for two weeks. Fifth group was given normal saline solution and serived as control The histopathological study showed pathological lesions in most of internal organs of the third group that infected with Escherichia coli bacteria specially liver, kidney and intestine. First group revealed lesions less than the third group, while the second group showed just aggregation of inflammatory cells in some internal organs and this refers that the ethanolic extract of Sonchus oleraceus have obvious inhibitory effect on Escherichia coli bacteria when compared with the infected group.